2020
DOI: 10.1002/rmv.2123
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology and immunotherapeutic strategies in severe acute respiratory syndrome coronavirus 2 infection

Abstract: Summary The outbreak of coronavirus disease 2019 (COVID‐19) and pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has become a major concern globally. As of 14 April 2020, more than 1.9 million COVID‐19 cases have been reported in 185 countries. Some patients with COVID‐19 develop severe clinical manifestations, while others show mild symptoms, suggesting that dysregulation of the host immune response contributes to disease progression and severity. In this review, we have summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 114 publications
(136 reference statements)
1
71
0
1
Order By: Relevance
“…One of the main mechanisms of escape by viruses, especially SARS-CoV, is the inhibition of IFN production as an anti-viral cytokine [ 133 , 134 ]. Membrane proteins of SARS-CoV can suppress adaptor molecules in the downstream of the IRFs signaling pathway, resulting in decreased IRF3/IRF7 transcription factor translocation and expression [ 135 ]. It is well known that cathepsins and proteasomes play the crucial roles in the MHC-I and -II pathways and processing of viral protein antigens.…”
Section: Influenza Virus and Sars-cov-2 Immune Evasion Mechanismsmentioning
confidence: 99%
“…One of the main mechanisms of escape by viruses, especially SARS-CoV, is the inhibition of IFN production as an anti-viral cytokine [ 133 , 134 ]. Membrane proteins of SARS-CoV can suppress adaptor molecules in the downstream of the IRFs signaling pathway, resulting in decreased IRF3/IRF7 transcription factor translocation and expression [ 135 ]. It is well known that cathepsins and proteasomes play the crucial roles in the MHC-I and -II pathways and processing of viral protein antigens.…”
Section: Influenza Virus and Sars-cov-2 Immune Evasion Mechanismsmentioning
confidence: 99%
“…However, the authors reported that CP treatment is potentially beneficial to critically ill patients by suggesting a possible antiviral efficiency of high titer of nAbs. Notably, there are clinical controversies, ethical issues, and potential risks associated with convalescent plasma therapy (275), such as the possibility of ADE development, exacerbating the disease severity, and causing a significant illness in future exposure to coronaviruses infection (268,276,277) (REF). Divergences between studies may be caused by variations in the composition of CP, which is highly variable and includes a variety of blood-derived components, timing of CP administration, titer of the specific antibody in administered plasma, and presence of blood borne pathogens (268).…”
Section: Antibody-based Therapymentioning
confidence: 99%
“…The search for effective therapies and vaccines is going on worldwide (7)(8)(9)(10). The large number of fatalities caused by SARS-CoV-2 attests to the severe global impact of the pandemic, irrespective of age, race, sex, and physiological conditions.…”
Section: Introductionmentioning
confidence: 99%